EFFECT OF CADMIUM EXPOSURE ON INCREASING RISK OF DIABETES MELITUS THROUGH THE MEASUREMENT OF BLOOD GLUCOSE LEVEL AND LIVER GLUCOKINASE ACTIVITY IN RATS - Thalib, Iskandar; Budianto, Windy Yuliana; Suhartono, Eko (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: This present study was undertaken to investigate the effect of cadmium (Cd) exposure on an increasing risk of Diabetes Melitus (DM), through the measurement of blood glucose level and liver glucokinase activity in rats. The subjects that used in this study are 15 male rats (Rattus novergicus) with normal activity, 2-3 months old, and weighing 300Â±10 gram. The research subjects the divided into 3 groups; P0 group are given commercial fed rats diets only; P1 are given commercial fed rats + Cd with a concentration of 3 mg/l in drinking water for 1 day (acute); and P2 are given commercial fed rats+Cd with a concentration of 3 mg/l in drinking water for 4 weeks (subacute). The results of this present study shows that treatment with Cd significantly increase the levels of blood glucose (P < 0,05). The result also showed that treatment with Cd can increase the Km value of liver glucokinase, and it means Cd exposure can decrease the affinity between glucose and glucokinase. The present study demonstrated that Cd exposure could increase the risk of DM through increased the blood glucose and decrease the activity of liver glucokinase.Â Keywords: Cadmium, glucose metabolism, glucose, glucokinase